Primary and Secondary Spontaneous Pneumothorax: Prevalence, Clinical Features, and In-Hospital Mortality. (13th March 2017) - Onuki, Takuya; Ueda, Sho; Yamaoka, Masatoshi; Sekiya, Yoshiaki; Yamada, Hitoshi; Kawakami, Naoki; Araki, Yuichi; Wakai, Yoko; Saito, Kazuhito; Inagaki, Masaharu; Matsumiya, Naoki
Abstract : Background . Optimal treatment practices and factors associated with in-hospital mortality in spontaneous pneumothorax (SP) are not fully understood. We evaluated prevalence, clinical characteristics, and in-hospital mortality among Japanese patients with primary or secondary SP (PSP/SSP). Methods . We retrospectively reviewed and stratified 938 instances of pneumothorax in 751 consecutive patients diagnosed with SP into the PSP and SSP groups. Factors associated with in-hospital mortality in SSP were identified by multiple logistic regression analysis. Results . In the SSP group (n = 327 ; 34.9%), patient age, requirement for emergency transport, and length of stay were greater (all, p < 0.001 ), while the prevalence of smoking (p = 0.023 ) and number of surgical interventions (p < 0.001 ) were lower compared to those in the PSP group (n = 611 ; 65.1%). Among the 16 in-hospital deceased patients, 12 (75.0%) received emergency transportation and 10 (62.5%) exhibited performance status (PS) of 3-4. In the SSP group, emergency transportation was an independent factor for in-hospital mortality (odds ratio 16.37; 95% confidence interval, 4.85–55.20; p < 0.001 ). Conclusions . The prevalence and clinical characteristics of PSP and SSP differ considerably. Patients with SSP receiving emergency transportation should receive careful attention.